2014
DOI: 10.1590/s1984-29612014040
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Borrelia in wild and domestic mammals from the state of Minas Gerais, Brazil

Abstract: The main of the study was to evaluate the presence of Borrelia burgdorferi infection in domestic and wild vertebrates and ectoparasites in endemic areas from the state of Minas Gerais, Brazil. A total of 445 serum samples were examined by ELISA, which used the Borrelia burgdorferi strain G39/40 U.S. source and 3,821 tick samples were tested by polymerase chain reaction (PCR). B. burgdorferi antibodies were found in 30 serum samples (6.74%); three in marsupials (7.69%), three in rodents (2.80%), nine in dogs (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Similar results were observed in the state of Minas Gerais, where the presence of antibodies against B. burgdorferi was detected in 7.69% opossums (MONTANDON et al, 2014). Other studies in Brazil have reported humans and animals seropositive for B. burgdorferi (YOSHINARI et al, 2010;CORRADI et al, 2006;MADUREIRA et al, 2007;MONTANDON et al, 2014), demonstrating different prevalence rates in dispersed areas and showing that both domestic and wild animals are becoming infected with a closely related Borrelia spp., although the agents have never been isolated in Brazil. Our findings reinforce the probable presence of these agents in opossums in eight municipalities in the state of São Paulo and emphasize the need for further research into these pathogens in this study area, in view of the occurrence of BSF and BYS in humans in the state of São Paulo.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were observed in the state of Minas Gerais, where the presence of antibodies against B. burgdorferi was detected in 7.69% opossums (MONTANDON et al, 2014). Other studies in Brazil have reported humans and animals seropositive for B. burgdorferi (YOSHINARI et al, 2010;CORRADI et al, 2006;MADUREIRA et al, 2007;MONTANDON et al, 2014), demonstrating different prevalence rates in dispersed areas and showing that both domestic and wild animals are becoming infected with a closely related Borrelia spp., although the agents have never been isolated in Brazil. Our findings reinforce the probable presence of these agents in opossums in eight municipalities in the state of São Paulo and emphasize the need for further research into these pathogens in this study area, in view of the occurrence of BSF and BYS in humans in the state of São Paulo.…”
Section: Discussionsupporting
confidence: 69%
“…This result may have been due to the high sensitivity (94.1%) and good specificity (96.2%) for specific antibodies to the C6 synthetic peptide to B. burgdorferi s.s. presented by the commercial rapid ELISA test used here. Alternatively, our findings may have been the consequence of a low tick infection rate (Spolidorio et al, 2010) or a conceivably different B. burgdorferi strain or a similar species in Brazil (Joppert et al, 2001;Montandon et al, 2014). Nonetheless, further studies should be conducted in order to fully establish the potential association between antibody presence and the zoonotic Brazilian Baggio-Yoshinari syndrome.…”
Section: Introductionmentioning
confidence: 90%
“…Thus, these animals should be continuously monitored as environmental sentinels for hemoplasmas and other CVBDs. Although seropositivity has been already reported in dogs, human beings and horses in Brazil, no molecular evidence of B. burgdorferi infection has been found to date (Joppert et al, 2001;Labarthe et al, 2003;Spolidorio et al, 2010;Montandon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Baggio-Yoshinary syndrome is a Brazilian zoonosis, a new tick borne disease caused by Borrelia spp, possibly a Borrelia burgdorferi sensu lato genetically modified or a new Borrelia species, transmitted by ticks of genus Amblyomma and Rhipicephalus [91,92]. The first case was described in 1992 in Brazil, initially as a case resembling LD, then called Baggio-Yoshinary syndrome because of some epidemiological, clinical, and laboratory differences from LD [93,94].…”
Section: Baggio-yoshinary Syndromementioning
confidence: 99%